Dynamic Virtual Environment Synthesis: Leveraging Machine Learning for Real-Time 3D Object Integration in VR Spaces - Pathak, Anshuman; Singh, Anmol Deep; Saregar, Antomi; Dixit, Aparna; Dewalkar, S. V.; Panse, V. R. (International Journal of Electronics and Communications Systems, 2025)
Existing VR environments relies on static asset libraries and predesigned scenarios, which limits personalization and fails to account for diverse user needs. This paper aims Dynamic Virtual Environment Synthesis (DVES), a new framework based on machine learning to generate and control a large library of 3D objects for real-time creation and context-aware adaptation. The research method categorizes the system design into five main components: data collection, preprocessing and annotation, machine learning model training, VR environment integration, and user interaction. DVES allows users to customize VR spaces through natural language, gestures, or biometric feedback, harnessing generative models for creating objects, reinforcement learning for adaptive environments, and neural rendering for adding realism, building foundation for the next-gen entertainment ecosystem. DVES improves gaming, training, therapy, and education by mediating static design and real-time systems. Unlike the existing conventional VR systems which depends on the static and prebuilt scenes, DVES continuously learns from user interactions, enabling the system to evolve dynamically. This novel study investigates scalability, real-time performance, and natural interfaces and provides insights into future applications, giving a custom VR experience to the users. In long term, DVES could serve as a foundation for fully autonomous VR ecosystems, creating a personalized and immersive digital experience. The study ensures transitioning VR from static, predesigned systems to self-sustaining, user-driven digital worlds.